DAMPAK PENGETATAN ILEGAL LOGING TERHADAP PERUBAHAN STRUKTUR PEKERJAAN DAN PENDAPATAN MASYARAKAT DI KECAMATAN SERUYAN HILIR KABUPATEN SERUYAN - Lili Winarti (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The objectives of the research were to analyze the structure of publik employment in Seruyan Hilir Sub-district of Seruyan Regency and to analyze the impact of changes in the structure of employment from illegal logging on the economical condition (total household income). It applied survey method using questioners to gather primary data, and the respondents had to work in forestry sector. In order to answer the first objective, the descriptive analysis method was applied while the measurement of the effects of the work transition applying the paired z-test (pre-post) was conducted to answer the second objective which examined the difference of the condition after and before the work transision. Result of descriptive analysis shows that the structure of the work is the choice of the respondents as a substitute source of their income is greatest in the services sector 26%, trading 19%, then agriculture 18% and fishery 18% and others like Civil Service, transportation and husbandry less than 10%. The average respondent’s income before doing work transition was Rp 2,012,124 per month and after work transition was Rp 839,703 per month. The z-test indicated that the calculated z-value was 0.000 indicating that there was a significant difference between the income earned by respondents before and after doing work transition.